Prediction of honey adulteration using machine learning-assisted OIRD - Shanzhe Zhang; Shunyi Li; Hao Yang; Enhao Tang; Xiaorong Sun; Yuan Gao; Cuiling Liu; Kun Zhao (Food Bioscience, 2026)

Multiscale characterization of the adsorption behavior at oil-water interface of β-cyclodextrin - Xiaorong Sun; Liyi Chen; Haoyue Zhang; Chonghao Bi; Cuiling Liu; Aoxue Qie; Kun Zhao; Shanzhe Zhang; Xuecong Liu (Journal of Food Engineering, 2026)

Climate-driven dynamics of surface water temperature and its coupled responses to lake heatwaves and cyanobacterial blooms in Lake Taihu - Lei Sun; Ruiting Xu; Yakun Feng; Haozhang Dai; Menglin Yuan; Chenhui Wu; Hao Wang; Ya Liu; Cuiling Jiang (Journal of Environmental Management, 2026)

Environmental effects of Shenhu gas hydrate trial production: A perspective on carbon cycling in shallow sediments - Taiheng Lv; Cuiling Xu; Zhilei Sun; Hong Cao; Xilin Zhang; Wei Geng; Ye Chen; Sinan Xu; Dong Zhang; Yucheng Zhou; Shixing Li; Yunbao Sun; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Genome-wide analysis of Zoysia japonica REVEILLE family identifies ZjRVE8-1 as a positive cold-tolerance regulator - Cuiling Liu; Liangliang He; Ming Jiang; Zhihao Wu; Jieyi Li; Chao Liu; Quanrui Su; Jingyi Sun; Fei Xu; Shu Chen (Plant Cell Reports, 2026)

Different AOM processes driving the formation of carbonate crusts and nodules in the Okinawa Trough - Yucheng Zhou; Hong Cao; Zhilei Sun; Wei Geng; Chenhui Liu; Xilin Zhang; Cuiling Xu; Taiheng Lv; Shixing Li; Ye Chen; Xuejun Jiang; Dong Zhang; et al. (Marine and Petroleum Geology, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

Single and mixture toxicity effects of legacy and emerging per- and polyfluoroalkyl substances on submerged plants and epiphytic biofilms - Yakun Feng; Cuiling Jiang; Wei Zhang; Lin Gong; Lei Sun (Journal of Hazardous Materials, 2025)

Genomic insights into the genetic basis of the seed size and weight revealed by the Chinese peanut key landraces - Juan Wang; Bingke Jiao; Chunjuan Qu; Caixia Yan; Dachuan Shi; Chen Jiang; Mei Yuan; Wenjiao Wang; Cuiling Yuan; Xiaobo Zhao; Quanxi Sun; Yifei Mou; et al. (Theoretical and Applied Genetics, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

A machine learning approach fusing multisource spectral data for prediction of floral origins and taste components of Apis cerana honey - Zhaolong Liu; Hongxia Li; Nan Liu; Cuiling Liu; Xiaorong Sun; Lanzhen Chen (Food Research International, 2025)

Spatial Heterogeneity of the Microbial Community in the Surface Sediments in the Okinawa Trough - Ye Chen; Nengyou Wu; Cuiling Xu; Youzhi Xin; Jing Li; Xilin Zhang; Yucheng Zhou; Zhilei Sun (Journal of Marine Science and Engineering, 2025)
The Okinawa Trough (OT) has been a focus of scientific research for many years due to the presence of vibrant hydrothermal and cold seep activity within its narrow basin. However, the spatial distribution and environmental drivers of microbial communities in OT sediments remain poorly understood. The present study aims to address this knowledge gap by investigating microbial diversity and abundance at ten different sampling sites in a transitional zone between hydrothermal vents and cold seeps in the OT. The microbial community at two sampling sites (G08 and G09) in close proximity to hydrothermal vents showed a high degree of similarity. However, lower bacterial and archaeal abundances were found in these sites. The archaeal groups, classified as Hydrothermarchaeota and Thermoplasmata, showed a comparatively higher relative abundance at these sites. In addition, ammonia-oxidizing archaea (AOA), from the family Nitrosopumilaceae, were found to have a higher relative abundance in the OT surface sediments at sampling sites G03, G04, G05, G06, and G07. This result suggests that ammonia oxidation may be actively occurring in these areas. Furthermore, Methylomirabilaceae, which are responsible for methane oxidation coupled with nitrite reduction, dominated three sampling sites (G07, G08, and G09), implying that N-DAMO may play an important role in mitigating methane emissions. Using the FAPROTAX database, we found that predicted prokaryotic microbial functional groups involved in methyl-reducing methanogenesis and hydrogenotrophic methanogenesis were most abundant at sites G08 and G09. At sampling sites G01 and G02, functional groups such as hydrocarbon degradation, methanotrophy, methanol oxidation, denitrification, sulfate respiration, and sulfur oxidation were more abundant. Nitrogen content is the most important environmental factor determining the bacterial and archaeal communities in the OT surface sediments. These results expand our knowledge of the spatial distribution of microbial communities in the transitional zone between hydrothermal vents and cold seeps in the OT.

Rapid and nondestructive identification of rice storage year using hyperspectral technology - Xiaorong Sun; Xinpeng Zhou; Cuiling Liu; Chunlin Li; Shanzhe Zhang; Dongyu Zheng (Food Control, 2025)

Response mechanisms of submerged macrophytes and epiphytic biofilms to single and coexisting per-and poly-fluoroalkyl substances and antibiotics stress - Yakun Feng; Cuiling Jiang; Wei Zhang; Lei Sun; Zequn Fan; Can Lu; Lei Jiang; Ruiting Xu; Ya Liu (Journal of Environmental Chemical Engineering, 2024)

Supply of Dissolved Organic Carbon from the Cold Seeps-Hydrothermal System and Its Impact on the Deep-Sea Carbon Cycle: An Overview - Xianrong Zhang; Zhilei Sun; Libo Wang; Xilin Zhang; Bin Zhai; Cuiling Xu (Journal of Ocean University of China, 2024)

Impacts of conventional and biodegradable microplastics on greenhouse gas emissions and microbial communities in lake sediment under diverse aging methods - Zequn Fan; Cuiling Jiang; Tahir Muhammad; Yakun Feng; Lei Sun; Lei Jiang; Can Lu (Journal of Cleaner Production, 2024)

Geochemistry of iron and trace metals in seep carbonates of the middle Okinawa Trough impacted by hydrothermal plumes - Shuang-Shuang Qin; Mao-Xu Zhu; Tie Li; Xilin Zhang; Cuiling Xu; Hong Cao; Wei Geng; Bin Zhai; Ye Chen; Shixing Li; Zhilei Sun (Chemical Geology, 2024)

A new approach to extract the upright maize straw from Sentinel-2 satellite imagery using new straw indices - Jingping Zhou; Xiaohe Gu; Cuiling Liu; Wenbiao Wu; Yuchun Pan; Qian Sun; Sen Zhang; Xuzhou Qu (Computers and Electronics in Agriculture, 2024)

Impacts and mechanism of biodegradable microplastics on lake sediment properties, bacterial dynamics, and greenhouse gasses emissions - Zequn Fan; Cuiling Jiang; Tahir Muhammad; Imran Ali; Yakun Feng; Lei Sun; Hui Geng (Science of The Total Environment, 2023)

Methane distribution and sea-to-air methane flux in the Dongsha area of the South China Sea - Cuiling Xu; Zhilei Sun; Qing Li; Xianrong Zhang; Xilin Zhang; Bin Zhai; Qiang Fu; Yuhai Sun; Wei Geng; Hong Cao; Ye Chen; Nengyou Wu (Continental Shelf Research, 2023)

Identification of the glutamine synthetase (GS) gene family in four wheat species and functional analysis of Ta4D.GSe in Arabidopsis thaliana - Huayan Yin; Qian Sun; Xiaoqing Lu; Lufei Zhang; Yanchao Yuan; Cuiling Gong; Xiaoyan He; Wujun Ma; Ping Mu (Plant Molecular Biology, 2022)
Drought stress can negatively impact crop yield and quality. Improving wheat yields under drought stress is a major objective of agronomic research. Glutamine synthetase (GS) is a key enzyme of nitrogen metabolism that is critical to plant growth and development in abiotic stress response. However, to date, no systemic characterization of the GS genes has yet been conducted in wheat and its close relatives. We identified a total of 15 GS genes in Triticum aestivum (2n = 6x = 42; AABBDD), as well as 9 GS genes in Triticum dicoccoides (2n = 4x = 28; AABB), 6 in Aegilops tauschii (2n = 2x = 14; DD), and 5 in Triticum urartu (2n = 2x = 14; AA). The 35 GSs were further clustered into five lineages according to the phylogenetic tree. Synteny analysis revealed that the three subgenomes in bread wheat retained extensive synteny between bread wheat and its three relative species. We identified three up-regulated TaGSs ( Ta4A.GSe , Ta4B.GSe , and Ta4D.GSe ) from transcriptome data after drought and salt stress. Ta4D.GSe was subsequently used for further functional studies, and its subcellular localization were determined in Arabidopsis protoplasts. Its overexpression in Arabidopsis enhanced drought tolerance by increasing the ability of scavenging of reactive oxygen species (ROS) and osmotic adjustment. We identified GS gene family in four wheat species and performed comparative analyses of their relationships, chromosome locations, conserved motif, gene structure, and synteny. The subcellular localization of Ta4D.GSe was detected and its drought tolerance function was demonstrated. Taken together, these findings provide insight into the potential functional roles of the GS genes in abiotic stress tolerance. Key message This report clearly shows detailed characterization of GS gene family in four wheat species and demonstrates that Ta4D.GSe plays an important role in enhancing drought tolerance by improving the scavenging of ROS and osmotic adjustment ability in Arabidopsis .

First report of brassica yellows virus infecting cowpea in China - Shunyu Xiang; Cuiling Tian; Changyun Liu; Haoran Peng; Jing Wang; Sihan Ye; Daibin Wang; Chen Xu; Xianchao Sun; Yang Xue (Journal of Plant Pathology, 2021)

Pore-water geochemistry in methane-seep sediments of the Makran accretionary wedge off Pakistan: Possible link to subsurface methane hydrate - Xianrong Zhang; Jianming Gong; Zhilei Sun; Jing Liao; Bin Zhai; Libo Wang; Xilin Zhang; Cuiling Xu; Wei Geng (Acta Oceanologica Sinica, 2021)

The biosynthesis of camptothecin derivatives by Camptotheca acuminata seedlings - Yanni Sun; Ning Zhang; Cuiling Wang; Xiao Bai; Yahui Wei; Jianli Liu (Natural Product Research, 2021)

Distribution of camptothecin biosynthetic intermediates and identification the rate-limiting step of camptothecin biosynthesis - Yanni Sun; Ning Zhang; Cuiling Wang; Yahui Wei; Jianli Liu (Natural Product Research, 2021)

Ochratoxin A induces nephrotoxicity in vitro and in vivo via pyroptosis - Hu Li; Xinru Mao; Kai Liu; Jiahao Sun; Benrui Li; Rahmani Mohammad Malyar; Dandan Liu; Cuiling Pan; Fang Gan; Yunhuan Liu; Kehe Huang; Xingxiang Chen (Archives of Toxicology, 2021)

A new phenolic glycoside from Trollius chinensis Bunge with anti-inflammatory and antibacterial activities - Jie Feng; Danyang Zhao; Qiannan Xu; Xiangzhong Liu; Mi Zhou; Xiansheng Ye; Ting Lin; Guanghui Wang; Cuiling Sun; Rong Ding; Wenjing Tian; Haifeng Chen (Natural Product Research, 2020)

Research Progress of Seafloor Pockmarks in Spatio-Temporal Distribution and Classification - Cuiling Xu; Guoqiang Xu; Junhui Xing; Zhilei Sun; Nengyou Wu (Journal of Ocean University of China, 2020)

Isolation and characterization of a novel seed-specific promoter from peanut (Arachis hypogaea L.) - Cuiling Yuan; Chunjuan Li; Caixia Yan; Xiaobo Zhao; Juan Wang; Quanxi Sun; Shihua Shan (Molecular Biology Reports, 2019)

Biotite weathering by Aspergillus niger and its potential utilisation - Weiying Wang; Jingjing Sun; Cuiling Dong; Bin Lian (Journal of Soils and Sediments, 2016)

Enhanced expression of the human CD14 protein in tobacco using a 22-kDa alpha-zein signal peptide - Xiuxia Liu; Li Sun; Cuiling Li; Aifang Yang; Juren Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)